PENDEKATAN ABCD (ASSET BASED COMMUNITY DEVELOPMENT) DALAM PEMBERDAYAAN MASYARAKAT MELALUI PELATIHAN PEMBENIHAN LELE UNTUK MENINGKATKAN KEMANDIRIAN PENDAPATAN MASYARAKAT - Yuni Purnama Sari; Muhammad Dharma Setiadi; Antis Martin Christianti; Asnaini; Robeet Thadi (STKIP Subang, 2026)
This community service initiative addresses the low technical skills in catfish breeding, external seed dependence, and weak business management among breeders in Padang Serai, Bengkulu. The program aims to empower partners as active subjects through catfish breeding training utilizing the Asset Based Community Development approach to enhance economic independence. The implementation method adopts five participatory ABCD stages, encompassing discovery, dream, design, define/destiny, plus monitoring and evaluation. Activities ran intensively for one and a half months, focusing on broodstock selection, controlled spawning, larva care, and water quality management using tarpaulin ponds. Service results demonstrate significant improvement in participant technical competency, establishment of independent business groups, and healthy seed production that reduces external supply reliance. Extreme weather challenges affecting water turbidity and unstructured financial recording habits remain crucial notes for future improvement. Overall, integrating local asset empowerment with participatory mentoring effectively transforms communities from passive objects into independent, sustainable catfish seed producers. These findings confirm that the ABCD approach remains highly relevant for micro and small enterprise scales. Future recommendations include water filtration, marketing digitalization, and financial literacy training. Continuous mentoring ensures appropriate technology adaptation and partner household income stability. Such interventions guarantee long-term sustainability and regional competitiveness for rural aquaculture sectors.